A dual role of EphB1/ephrin-B3 reverse signaling on migrating striatal and cortical neurons originating in the preoptic area: should I stay or go away? - Rudolph, Judith; Gerstmann, Katrin; Zimmer, Geraldine; Steinecke, André; Döding, Annika; Bolz, Jürgen (Frontiers in Cellular Neuroscience, 2014)
During embryonic development the preoptic area (POA) gives rise to two populations of neurons which are generated at the same time, cortical interneurons and striatal cells. POA-derived cortical interneurons take a superficial path and avoid the developing striatum when they migrate to their target region. We found that EphB1, which is expressed in the striatal anlage, prevents cortical interneurons from entering the striatum via ephrin-B3 reverse signaling. In contrast, for striatal neurons which also express ephrin-B3, EphB1 acts as a stop signal. This dual role of EphB1 is due to differences in ephrin-B3 reverse signaling cascades. For striatal neurons, binding of EphB1 to ephrin-B3 reduces endogenously high levels of pSrc and pFAK, which then causes the cells to stop migration. In contrast, in cortical interneurons EphB1-ephrin-B3 reverse signaling leads to phosphorylation of Src and FAK which then mediates repulsion. Consistent with these in vitro findings, in an ephrin-B3 knockout mouse line, we discovered misrouted cortical interneurons in the striatum and an over-migration of striatal neurons in their target region. Thus, EphB1/ephrin-B3 reverse signaling has a different impact on two sets of neurons which are generated at the same time and place: it can act as a repulsive cue for migrating neurons or it can terminate neuronal migration, a novel role of the Eph/ephrin system.